IMPLEMENTATION OF ANIMATED MEDIA TO INCREASE THE INTEREST OF STUDENTS IN PGII 2 HIGH SHOOL BANDUNG - Nazmi, Muhammad (Jurnal Pendidikan Geografi Gea, 2017)
Various challenges in teaching geography in improving the quality of learning to do, which is one attempt to see the learning styles of learners are using the media into the learning activities. Media that can be used include: media animation. Media animations with the excess that is in addition to ease in understanding the material that is difficult to understand, it can also increase the motivation and interests of learners. Application of the animation medium in a study aimed to increase the interest of learners in class XI SMA PGII-2 Bandung. The research method uses classroom action research design John Elliot that there are three acts in its cycle. The technique of collecting data through observation and test sheets. The results showed an increase in aspect and action. Aspects of the first actions interests of learners ie 48.38% increase in the second act of reaching an average of 80.31%. Then in the third act to increase reach an average of 92.53%. This happens because the application of animation media is much more effective in attracting the attention and concentration of students in learning. If the interests of learners high and very enthusiastic in learning it would be easy to understand learning, learning outcomes will be better, and learning objectives can be achieved in accordance with the desired.